2023
DOI: 10.3389/fpubh.2022.1076248
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 epidemic and public health interventions in Shanghai, China: Statistical analysis of transmission, correlation and conversion

Abstract: BackgroundThe Shanghai COVID-19 epidemic is an important example of a local outbreak and of the implementation of normalized prevention and disease control strategies. The precise impact of public health interventions on epidemic prevention and control is unknown.MethodsWe collected information on COVID-19 patients reported in Shanghai, China, from January 30 to May 31, 2022. These newly added cases were classified as local confirmed cases, local asymptomatic infections, imported confirmed cases and imported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In contrast to Chengdu and Beihai, Shanghai and Sanya did not respond promptly and effectively when the outbreak was initially detected, especially in Shanghai, where the government did not implement city-wide nucleic acid testing and widespread control until nearly a month after the virus had spread [ 30 ]. After modeling the Omicron outbreak in Shanghai in 2022, Yi et al suggested that the course of the epidemic will depend on the efficiency of the implementation of public health interventions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Chengdu and Beihai, Shanghai and Sanya did not respond promptly and effectively when the outbreak was initially detected, especially in Shanghai, where the government did not implement city-wide nucleic acid testing and widespread control until nearly a month after the virus had spread [ 30 ]. After modeling the Omicron outbreak in Shanghai in 2022, Yi et al suggested that the course of the epidemic will depend on the efficiency of the implementation of public health interventions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of public emergencies, the normal public governance approach is facing many challenges, such as the frequent failure of digital governance platforms [2], the increase in systemic financial risk crises [3] and the surge in public fears [4]. To address these challenges, scholars have conducted a series of studies to promote policy coordination and enhance governance efficiency.Ref.…”
Section: Related Research 21 Research On Public Emergenciesmentioning
confidence: 99%
“…NPIs are aimed at reducing SARS-CoV-2 transmission and are likely to impact the epidemiology of other respiratory viruses [ 10 ]. In December 2022, the National Health Commission of the People's Republic of China announced that 2019‐nCoV pneumonia preventive and control measures were taken according to category B infectious diseases [ 11 ]. Research shows that multiple respiratory viruses can concurrently or sequentially infect the respiratory tract and lead to virus‒virus interactions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%